2019
DOI: 10.35940/ijrte.c5832.098319
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Various Natural Ester Oils Impregnated Nomex Paper Performance in Power Transformer Applications under Different Ageing Conditions

Abstract: Vegetable oils are being considered as the potential replacements to mineral oils because of their better natural execution and for their high fire point. In spite of the fact that these fluids have been utilized as a part of appropriation transformers, it is as yet a huge advance to receive vegetable oils in control transformer because of high cost and abnormal state of well being and unwavering quality required in benefit for these units. Vegetable oils such as honge oil (HO), neem oil (NO), mustard oil (MO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As a result, the backbone of the benzene ring structure for aramid molecular is broken, which causes the molecular weight of the aramid molecular to decrease, affecting the mechanical properties of the oil-impregnated Nomex paper. [22][23][24][25] Figure 8 shows the content of carbon and oxygen in oilimpregnated Nomex paper based on EDS. It can be seen that the atomic and mass percentage of carbon are the lowest and the atomic and mass percentage of oxygen are the highest for the blank sample.…”
Section: Chemical Properties Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the backbone of the benzene ring structure for aramid molecular is broken, which causes the molecular weight of the aramid molecular to decrease, affecting the mechanical properties of the oil-impregnated Nomex paper. [22][23][24][25] Figure 8 shows the content of carbon and oxygen in oilimpregnated Nomex paper based on EDS. It can be seen that the atomic and mass percentage of carbon are the lowest and the atomic and mass percentage of oxygen are the highest for the blank sample.…”
Section: Chemical Properties Analysismentioning
confidence: 99%
“…It can also be observed that the position and shape of the diffraction peaks before and after PD degradation remain basically unchanged, and that only the intensity of the diffraction peak changes. In order to further analyze the influence of high frequency on the aggregation structure of oil-paper insulation, the integral method [23][24][25] has been used to calculate the crystallinity of the paper, as shown in Table II. The corresponding calculation formula is expressed as:…”
Section: Xrd Analysismentioning
confidence: 99%
“…The silica gel device as a dehumidifier in the transformer is a function of the load and environmental conditions. In addition, the volume of the dehumidifier is determined by the same factors [21,22]. The types of tests of these oils are divided into four categories including at least 28 typical tests according to the following cases.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of electrical and physicochemical properties of different vegetable oils with different ageing has been studied [6]. Due to lack of oxidative stability, the vegetable oils are less exposed as dielectric in transformer application [7].…”
Section: Introductionmentioning
confidence: 99%